Effects of tablet‐based drawing and paper‐based methods on medical students' learning of gross anatomy. Issue 2 (19th December 2022) - Styn, Amelie; Scheiter, Katharina; Fischer, Martin R.; Shiozawa, Thomas; Behrmann, Felix; Steffan, Adrian; Kugelmann, Daniela; Berndt, Markus
Abstract: The way medical students learn anatomy is constantly evolving. Nowadays, technologies such as tablets support established learning methods like drawing. In this study, the effect of drawing on a tablet on medical students' anatomy learning was investigated compared to drawing or summarizing on paper. The quality of drawings or summaries was assessed as a measure of the quality of strategy implementation. Learning outcome was measured with an anatomy test, both immediately afterward and after 4–6 weeks to assess its sustainability. There were no significant group differences in learning outcome at both measurement points. For all groups, there was a significant medium strength correlation between the quality of the drawings or summaries and the learning outcome ( p  < 0.05). Further analysis revealed that the quality of strategy implementation moderated outcomes in the delayed test: When poorly implemented, drawing on a tablet ( M  = 48.81) was associated with lower learning outcome than drawing on paper ( M  = 58.95); The latter ( M  = 58.89) was related to higher learning outcome than writing summaries ( M  = 45.59). In case of high‐quality strategy implementation, drawing on a tablet ( M  = 60.98) outperformed drawing on paper ( M  = 52.67), which in turn was outperformed by writing summaries ( M  = 62.62). To conclude, drawing on a tablet serves as a viable alternative to paper‐based methods for learning anatomy if students can make adequate use of this strategy. Future research needs to identify how to support student drawing, for instance, by offering scaffolds with adaptive feedback to enhance learning.